Dietary supplementation of Astragalus flavonoids regulates intestinal immunology and the gut microbiota to improve growth performance and intestinal health in weaned piglets - Che, Yuyan; Li, Lu; Kong, Mengjie; Geng, Yiwen; Wang, Dong; Li, Bin; Deng, Lufang; Chen, Guoshun; Wang, Jing (Frontiers in Immunology, 2024)
Astragali Radix (AS) is a widely used herb in traditional Chinese medicine, with calycosin as its main isoflavonoid. Our previous study discovered that calycosin triggers host defense peptide (HDP) production in IPEC-J2 cells. The aim of this study is to investigate the alleviation effects of AS total flavone and AS calycosin on growth performance, intestinal immunity, and microflora in weaned piglets. Sixty-four piglets were assigned randomly to 4 treatment groups, (1) CON: the basal diet, (2) P-CON: the basal diet plus antibiotics (1 g/kg), (3) AS-TF: the basal diet plus AS total flavone at 60 mg/day per piglet, (4) AS-CA: the basal diet plus AS calycosin at 30 mg/day per piglet.Each treatment consists of 4 replicates with 4 piglets per replicate. Results showed that treatment with AS-TF and AS-CA enhanced average daily growth and average daily feed intake compared to the CON group (P < 0.01), while AS-CA significantly reduced the diarrhea rate (P < 0.05). Both AS-TF and AS-CA significantly increased serum immunoglobulin (Ig) A and IgG levels, with AS-CA further boosting intestinal mucosal secretory IgA levels (P < 0.05). Histological analysis revealed improvements in the morphology of the jejunum and ileum and goblet cell count by AS-TF and AS-CA (P < 0.05). Supplementation of AS-TF and AS-CA promoted the expression of several intestinal HDPs (P < 0.05), and the effect of AS-CA was better than that of AS-TF. In addition, the AS-TF and AS-CA regulated jejunal microbial diversity and composition, with certain differential bacteria genera were showing high correlation with serum cytokines and immunoglobulin levels, suggesting that the intestinal flora affected by AS-TF and AS-CA may contribute to host immunity. Overall, AS CA and AS TF all improved growth performance and health, likely by enhancing nutrition digestibility, serum and intestinal immunity, and intestinal microbial composition. They showed the similar beneficial effect, indicating AS CA appears to be a major compound contributing to the effects of AS TF. This study demonstrated the positive effect of AS flavonoids on weaned piglets and provided a scientific reference for the efficient use of AS products.